Analysis of Regional Tax and Regional Retribution Contributions in Efforts to Increase Medan City's Original Regional Income 2020-2024 - Alfarizie, M. Mahdi Saman; Junawan, Junawan (Journal of Economics and Social Sciences (JESS), 2025)
This study analyzes the contribution and effectiveness of restaurant tax in strengthening local revenue (PAD) in Medan City during 2020–2024. The research is motivated by the strategic role of the culinary sector as one of the pillars of urban economic activity and its potential as a sustainable source of fiscal capacity. Using a descriptive-analytical approach with mixed methods, data were obtained from secondary reports of the Regional Revenue Agency (BAPENDA) and primary insights from key stakeholders. The results reveal that restaurant tax consistently contributed more than 10% of PAD throughout the study period, peaking at 16.82% in 2023. This growth was driven by post-pandemic economic recovery, increasing community mobility, and the implementation of digital tax systems such as tapping box and e-SPTPD. Although the contribution slightly decreased to 15.52% in 2024, this was not due to sectoral decline but to diversification of other PAD sources. In terms of effectiveness, tax collection rose from a low level in 2020–2021 (76.9%) to above 90% in 2023–2024, indicating significant improvement in compliance and efficiency. The study concludes that restaurant tax plays a dual role: as a resilient revenue source and as a driver of fiscal modernization through digital transformation. Policy implications emphasize expanding digitalization, fostering taxpayer education for MSMEs, and diversifying PAD to reduce dependency on a single sector. These findings provide both theoretical insights into local tax governance and practical recommendations for fiscal policy in developing urban economies.